Pemberdayaan keluarga melalui program home visit dalam pengelolaan penyakit kronis di Klinik Pratama Seno Medika Bandung - Fifi Veronica; Galih Priarti; Fauzi A Buntoro; Raihan H. L. Herdian; M. Farrell Al Ariq; Moudy B. Gularti; Neilsen L. Lo; Aurellia F. Syofian; R. Nadine T. Situmorang; Irna A.; Warda A. (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Chronic diseases are health problems that require holistic and long-term management. The success of therapy is influenced by various factors, including the patient's clinical condition, family support, socioeconomic status, health behaviors, and the condition of caregivers. Family empowerment through a home visit program is considered one of the primary healthcare strategies that enables a more comprehensive identification of factors affecting chronic disease management. This community service activity aimed to describe the biopsychosocial factors influencing the successful management of chronic diseases through home visits and community-based health assistance. The program was conducted through home visits to Prolanis patients under the care of Seno Medika Clinic Bandung who attended routine follow-up visits less than three times a year (<3 visits/year) during February–March 2026. Data were collected through semi-structured interviews, home environment observations, simple physical examinations, and discussions with family members. The findings were analyzed narratively based on clinical, social, health behavior, and family dynamics aspects. The results showed that chronic disease management was influenced by family dynamics and the role of caregivers, differences in individual self-management abilities, psychological conditions, and patients' knowledge of their disease. At the end of each visit, educational sessions were provided to patients, family members, and caregivers based on the identified problems. Home visits were able to identify various health determinants that were not detected through facility-based healthcare services. A family-centered approach and caregiver empowerment are essential components of chronic disease management to improve patients' quality of life and prevent further deterioration in the health of other family members.